2021
DOI: 10.1186/s44149-021-00029-1
|View full text |Cite
|
Sign up to set email alerts
|

Development of an accurate lateral flow immunoassay for PEDV detection in swine fecal samples with a filter pad design

Abstract: Porcine epidemic diarrhea virus (PEDV), as the main causative pathogen of viral diarrhea in pigs, has been reported to result in high morbidity and mortality in neonatal piglets and cause significant economic losses to the swine industry. Rapid diagnosis methods are essential for preventing outbreaks and transmission of this disease. In this study, a paper-based lateral flow immunoassay for the rapid diagnosis of PEDV in swine fecal samples was developed using stable color-rich latex beads as the label. Under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…[8] Immunoassays are popular alternatives to PCR for PEDv detection, which reduce sample-to-result time and assay complexity by eliminating the need for reverse transcription and target amplification. These assays rely on the use of antibodies as bio-recognition elements and are often integrated into engineered detection platforms or devices for rapid testing such as lateral flow assays (LFAs), [9][10][11] enzyme-linked immunosorbent assays (ELISA), [12][13][14][15][16][17] and electrochemical assays. [18][19][20] Although rapid, these methods, all based on antibody-based sandwich assays, either require multi-step processing such as washing, labeling, or addition of reagents (ELISA and electrochemical assays) or suffer from low clinical sensitivity and specificity partly stemming from the poor stability and crossreactivity of the antibodies (LFAs).…”
Section: Introductionmentioning
confidence: 99%
“…[8] Immunoassays are popular alternatives to PCR for PEDv detection, which reduce sample-to-result time and assay complexity by eliminating the need for reverse transcription and target amplification. These assays rely on the use of antibodies as bio-recognition elements and are often integrated into engineered detection platforms or devices for rapid testing such as lateral flow assays (LFAs), [9][10][11] enzyme-linked immunosorbent assays (ELISA), [12][13][14][15][16][17] and electrochemical assays. [18][19][20] Although rapid, these methods, all based on antibody-based sandwich assays, either require multi-step processing such as washing, labeling, or addition of reagents (ELISA and electrochemical assays) or suffer from low clinical sensitivity and specificity partly stemming from the poor stability and crossreactivity of the antibodies (LFAs).…”
Section: Introductionmentioning
confidence: 99%
“…In this systematic review and meta-analysis, we identified 11 articles of ICA-based POCTs published since 2015, and 2 of them used portable strip readers to analyze the detection results of ICA [ 19 , 21 ]. Moreover, a smartphone camera and immunofluorescent analyzer were also applied to quantify the results of ICA for detecting PEDV [ 18 , 22 ]. These handheld instruments provide convenient tools for reading the information of the ICA strip and make the results more precise, objective, and sensitive.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that there was no significant heterogeneity factor in our subgroup analysis in relation to sample type. It is well known that the fecal–oral route is believed to be the primary mode of PEDV transmission; feces are considered a rapidly obtainable and readily available sample for PEDV detection [ 18 , 46 ]. When comparing the diagnostic performance of ICA-based POCTs for different sample types, however, we found that the overall sensitivity of the feces sample was lower than that of other types of samples including rectal swab, small intestine, colostrum, and serum (0.95 vs. 0.96; p = 0.00), which revealed that the diagnostic performance of feces specimen was not necessarily superior to other specimens in ICA-based POCTs for PEDV infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations